Go ahead, grow a head! A planarian's guide to anterior regeneration. Issue 3 (24th June 2016) - Owlarn, Suthira; Bartscherer, Kerstin
Abstract: The unique ability of some planarian species to regenerate a head de novo, including a functional brain, provides an experimentally accessible system in which to study the mechanisms underlying regeneration. Here, we summarize the current knowledge on the key steps of planarian head regeneration (head‐versus‐tail decision, anterior pole formation and head patterning) and their molecular and cellular basis. Moreover, instructive properties of the anterior pole as a putative organizer and in coordinating anterior midline formation are discussed. Finally, we highlight that regeneration initiation occurs in a two‐step manner and hypothesize that wound‐induced and existing positional cues interact to detect tissue loss and together determine the appropriate regenerative outcomes.